Analysis of Factors Affecting the Technical Efficiency of Rice Farming in East Java Province - Rachman Hakim; Tri Haryanto; Dyah Wulan Sari (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2020)
Agriculture is a dominant sector in Indonesia, mostly because many people work in this sector, especially in agricultural centers such as East Java Province. However, it is ironic that the farm sector does not have a considerable contribution to Indonesia's national income. This study aimed to measure rice farming's efficiency in East Java and determine whether education, access to credit, farmer group membership, age, and agricultural extension affected rice farming efficiency. The data source comes from the Central Statistics Agency (Agricultural Business Household Income Survey) in 2013 for East Java Province. The number of samples used was 8603 farmer households. The research method uses Stochastic Frontier Analysis. The results showed that the average efficiency for the Cobb-Douglas production function was 0.764, while the average efficiency for the translog production function was 0.759. The Cobb-Douglas production function is not suitable for this study; the translog production function is considered more appropriate. The variables of education, access to credit, membership of farmer groups, age, and agricultural extension significantly influence rice farming's technical efficiency in East Java. The extension variable has the most significant effect.